ELEVATING STUDENTS' COMPETENCE BASED ICT IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Kurniawan Arizona (Journal of Teaching and Learning Physics, 2020)
This study aims to determine the increase in the competence of the Physics Education Students of UIN Mataram in the Physics Learning Innovation Course based on information technology in the Industrial Revolution Era 4.0. Participants in the study were Semester V and VII Students of the Study Program of Physics Education. This type of research is qualitative research. Data collection techniques in this study are the form of observation (participant performance), product assessment rubrics, and filling out questionnaires, which are described descriptively in the form of documentation, field notes, and participant actions. This study was directed in Odd Semester Academic Year 2019/2020. The instruments used included 1) observation sheet of student activities, 2) instrument performance test; 3) midterm test instruments, and final semester exams. The results showed that information technology-based learning could improve the competency of  Physics Education FTK UIN Mataram Students. Mainly their skills in the use of information technology in the form of using the google classroom application. They were making video learning using the Windows Live Movie Maker and video scribe (Sparkol) software, making learning blogs, making posters/learning leaflets, making computer-based test instruments (CBT), and the Physics Learning Innovation YouTube channel. These findings are reinforced by the final results of the average student score of 89.33 (A), with a standard deviation is 1.48, and excellent student response.